Synthesis and evaluation of N-(4-(substituted)-3-(trifluoromethyl) phenyl) isobutyramides and their N-ethyl analogous as anticancer, anti-angiogenic & antioxidant agents: In vitro and in silico analysis. (June 2021) - Sawant, Ajay S.; Kamble, Sonali S.; Pisal, Parshuram M.; Sawant, Sanjay S.; Hese, Shrikant V.; Bagul, Kamini T; Pinjari, Rahul V.; Kamble, Vinod T.; Meshram, Rohan J.; Gacche, Rajesh N.
Graphical abstract: Highlights: Novel flutamide derivatives were synthesized. Biological assessment of all compounds was done in the form of cytotoxic, anti-angiogenic and antioxidant activities. In-Silico study was performed. Abstract: N-(4-(substituted)-3-(trifluoromethyl) phenyl) isobutyramides and their N-ethyl analogues (flutamides) are versatile scaffolds with a wide spectrum of biological activities. A series of new N-(4-(substituted)-3-(trifluoromethyl) phenyl) isobutyramides (8a-t) and their N-ethyl analogous (9a-t) were synthesized and characterized. The inhibitory potential of the synthesized compounds on the viability of three human cancer cell lines HEP3BPN 11 (liver), MDA-MB 453 (breast), and HL 60 (leukemia) were assessed. Among all the compounds 8 L, 8q, 9n and 9p showed higher inhibitory activity on the viability of HL 60 than the standard methotrexate. These lead molecules were then tested for their potential to inhibit the activity of proangiogenic cytokines. The compound 9n showed significantly better inhibition against two cytokines viz. TNFα and Leptin as compared to the standard suramin, while 9p has activity comparable to suramin against IGF1, VEGF, FGFb, and Leptin. The 8q is found to be strong antiangiogenic agent against IGF1, VEGF and TGFβ; while 8 L has showed activity against TNFα, VEGF, and Leptin inhibition. Furthermore antioxidant potential of 8a–t and 9a-t compounds was screened using DPPH, OH and SOR radical scavenging activities. The OH radical scavenging activity of 8c and DPPH activities of 9n as well as 9o are significant as compared to respective standards ascorbic acid and α-tocopherol. The 8c, 9p and 9 h have also exhibited potential antioxidant activity. Additionally, we present in silico molecular docking data to provide the structural rationale of observed TNFα inhibition against newly synthesized compounds. Overall, the synthesized flutamide derivatives have not only anticancer activity, but also possess dual inhibitory effect (anti-angiogenesis and antioxidant) and hence can act as a promising avenue to develop further anticancer agents.